Cornsilk Fly (suggested common name), Euxesta stigmatias Loew (Insecta: Diptera: Otitidae) - Gregg S. Nuessly; John L. Capinera (EDIS)
The 'cornsilk fly,' Euxesta stigmatias Loew, is an attractive, dark metallic green fly with distinctive wing patterns and wing flapping behavior commonly found throughout southern Florida agricultural communities. Its normally saprophytic life style belies its destructive nature when it comes to its preference for sweet corn ears. Entire fields may have to be passed up for harvest if they went untreated for this destructive pest or if individual treatments were missed due to weather, time or other constraints. This document is EENY-224, one of a series of the Department of Entomology and Nematology, UF/IFAS Extension. Original publication date August 2001. Revised July 2005.